Grasping with the Press of a Button: Grasp-selective Responses in the Human Anterior Intraparietal Sulcus Depend on Nonarbitrary Causal Relationships between Hand Movements and End-effector Actions - Frey, Scott H. (J Cogn Neurosci, 2014)
Evidence implicates ventral parieto-premotor cortices in representing the goal of grasping independent of the movements or effectors involved [Umilta, M. A., Escola, L., Intskirveli, I., Grammont, F., Rochat, M., Caruana, F., et al. When pliers become fingers in the monkey motor system. Proceedings of the National Academy of Sciences, U.S.A., 105, 2209–2213, 2008; Tunik, E., Frey, S. H., & Grafton, S. T. Virtual lesions of the anterior intraparietal area disrupt goal-dependent on-line adjustments of grasp. Nature Neuroscience, 8, 505–511, 2005]. Modern technologies that enable arbitrary causal relationships between hand movements and tool actions provide a strong test of this hypothesis. We capitalized on this unique opportunity by recording activity with fMRI during tasks in which healthy adults performed goal-directed reach and grasp actions manually or by depressing buttons to initiate these same behaviors in a remotely located robotic arm (arbitrary causal relationship). As shown previously [Binkofski, F., Dohle, C., Posse, S., Stephan, K. M., Hefter, H., Seitz, R. J., et al. Human anterior intraparietal area subserves prehension: A combined lesion and functional MRI activation study. Neurology, 50, 1253–1259, 1998], we detected greater activity in the vicinity of the anterior intraparietal sulcus (aIPS) during manual grasp versus reach. In contrast to prior studies involving tools controlled by nonarbitrarily related hand movements [Gallivan, J. P., McLean, D. A., Valyear, K. F., & Culham, J. C. Decoding the neural mechanisms of human tool use. Elife, 2, e00425, 2013; Jacobs, S., Danielmeier, C., & Frey, S. H. Human anterior intraparietal and ventral premotor cortices support representations of grasping with the hand or a novel tool. Journal of Cognitive Neuroscience, 22, 2594–2608, 2010], however, responses within the aIPS and premotor cortex exhibited no evidence of selectivity for grasp when participants employed the robot. Instead, these regions showed comparable increases in activity during both the reach and grasp conditions. Despite equivalent sensorimotor demands, the right cerebellar hemisphere displayed greater activity when participants initiated the robot’s actions versus when they pressed a button known to be nonfunctional and watched the very same actions undertaken autonomously. This supports the hypothesis that the cerebellum predicts the forthcoming sensory consequences of volitional actions [Blakemore, S. J., Frith, C. D., & Wolpert, D. M. The cerebellum is involved in predicting the sensory consequences of action. NeuroReport, 12, 1879–1884, 2001]. We conclude that grasp-selective responses in the human aIPS and premotor cortex depend on the existence of nonarbitrary causal relationships between hand movements and end-effector actions.